АНАЛІЗ СИРОВИННОЇ ТА ТЕХНОЛОГІЧНОЇ БАЗИ ДЛЯ ВИРОБНИЦТВА ДИЗЕЛЬНОГО БІОПАЛИВА В УКРАЇНІ - Drahniev, S.V.; Zheliezna, T.A. (Institute of Engineering Thermophysics of NAS of Ukraine, 2024)
The purpose of the work is to develop recommendations for the possibility of renewing the production and consumption of biodiesel in Ukraine with the subsequent increase in the production of hydrotreated vegetable oil. The current state and prospects of diesel biofuel production in the world are analyzed. Production technologies and fuel characteristics of biodiesel and hydrotreated vegetable oil are considered. Over the past twenty years, the global production of diesel biofuel has increased from 2 to 55 billion l/year. Currently, about a third of the total production volume is in the EU. Diesel biofuel is divided into two types, namely biodiesel and hydrotreated vegetable oil. They differ in production technology and chemical composition. Now, biodiesel, which is fatty acids methyl ethers, is the type of diesel biofuel that is mainly produced and consumed in the world. However, given the fuel characteristics and ease of use, in the future, it makes sense to switch to hydrotreated vegetable oil, which is actually a complete analogue of diesel fuel. In Ukraine, during at least the last decade, the production and consumption of biodiesel has been practically absent. Despite this, there are certain prerequisites for the possibility of developing this direction in the future. Such prerequisites include availability of a large feedstock base, as well as significant groundwork in this field. We consider it expedient to establish a legislatively mandatory share of biodiesel in diesel fuel consumed in Ukraine at the level of 5%; introduce an export duty on rapeseed; cancel the excise tax on diesel biofuel; introduce a system for collecting used cooking oil; resume methanol production in Ukraine; create a specialized laboratory for testing biodiesel quality properties according to current international standards. To implement the proposed measures, we recommend the development of a new program for diesel biofuel production in Ukraine or the inclusion of a respective section in existing or planned national strategic documents.